A novel approach for measuring ultra-thin, buried SiO2 film thickness - Jiang, Z. X.; Sieloff, D. D. (Surface and interface analysis, 2009)
Accurate measurement of physical thickness of thin SiO2 films is of great interest to the semiconductor industry. Existing inspection techniques are subject to large error when the oxide thickness falls below 2 nm. This work explored a new approach with improved accuracy to the measurement of thickness of thin oxide films. The new method utilizes dynamic SIMS with a primary ion beam of one isotope of oxygen (16O or 18O) at normal incidence and detecting negative secondary ions of another isotope (18O or 16O, respectively) inside SiO2. The experiment was performed by using an 16O2+ primary beam and detecting 18O− as characteristic secondary ions for SiO2. We substantiated that the matrix effect was eliminated during profiling through the SiO2/Si interface in a poly Si/SiO2/Si stack with an O2+ beam at normal incidence, which is crucial for reliable quantification of oxygen amount inside SiO2. The high ion yield of 18O− and negligible contribution from the mass interference of16 OH2− ensured measurement of the total amount of oxygen inside an SiO2 film with good sensitivity. By assuming that the silicon oxide is in the form of stoichiometric SiO2, which is the case for those layers grown with dry oxidation, the measured amount of oxygen can be readily converted into the thickness of SiO2. This technique provides reproducible measurement of the thickness of SiO2 films and potentially a good accuracy if a reference material is well calibrated. Copyright © 2009 John Wiley & Sons, Ltd.